Asphalt-based hard carbon negative electrode material and preparation method and application thereof
Through the method of preparing asphalt-based hard carbon negative electrode materials, the problems of long process flow and large energy consumption in the existing technology are solved, and the effects of short process flow and low production cost are achieved, the reversible capacity and service life of new energy batteries are improved, and the safety is enhanced.
Patent Information
- Application Number
- CN202411195706.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-04-15
AI Technical Summary
The process flow of existing lithium-ion battery negative electrode materials is long and the energy consumption of heat treatment is large, resulting in high production costs and is not suitable for large-scale industrial production.
By using the preparation method of asphalt-based hard carbon negative electrode material, an oxidation reaction is performed by mixing the asphalt raw material, an organic solvent and an oxidizing agent to obtain the asphalt-based hard carbon precursor, and then mixing it with the negative electrode material and the solvothermal reaction solvent for solvothermal reaction. After boiling and washing with the acid solution, the asphalt-based hard carbon negative electrode material is obtained.
The process of this method is short and the production cost is low. The prepared asphalt-based hard carbon negative electrode material has the characteristics of high surface cladding, uniform cladding and small cladding particles. It is easy to achieve industrial application, and can improve the reversible capacity and service life of new energy batteries and improve safety.
Smart Images

Figure CN119822353A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy battery production, and specifically relates to an asphalt-based hard carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] With the development of the automobile industry, the depletion of non-renewable fossil fuels such as oil and natural gas has received increasing attention, and air pollution and greenhouse effects have also become global problems. In order to solve energy problems and achieve a low-carbon economy, based on the current development level of new energy technologies, electric vehicle technology has gradually become a key direction for global economic development. As a core component of electric vehicles, power batteries have also ushered in great development opportunities. Power batteries refer to batteries used in electric vehicles, including lithium-ion batteries, lead-acid batteries, fuel cells, etc. Among them, lithium-ion batteries have become the focus of development in various countries due to their high specific energy, high specific power, low self-discharge, long service life and good safety. Lithium-ion power battery negative electrode materials are mainly used in electric vehicles, power tools, mining rescue capsules, wind power generation energy storage power stations, and solar power generation energy storage power stations.
[0003] Coated asphalt is neutral, heat-resistant, light-resistant, water-resistant, weakly acidic and alkali-resistant, and has good electrical insulation properties. It has good compatibility with most organic solutions, oils, and waxes. It can be used as a coating agent and binder in the production and processing of negative electrode materials for lithium batteries. It has good mechanical properties, chemical stability, and high-temperature properties. It can improve the comprehensive performance of lithium-ion batteries in terms of isolating the positive and negative electrodes of the battery, allowing lithium ions to pass through, and preventing battery explosions caused by high temperatures, and improve energy density, environmental protection, and safety. Although coated asphalt has good physical and chemical properties, its electrochemical properties after coating the negative electrode material are also affected by the coating method and process.
[0004] Patent CN117776148A discloses "an asphalt-based sodium negative electrode material and its preparation method and application". This method mixes asphalt and a template agent, and obtains the negative electrode material by melting, air oxidation, argon carbonization, pickling, and vapor precipitation. This negative electrode material has a high initial coulombic efficiency and capacity, but the process flow is long and the energy consumption of heat treatment is large. Patent CN118145620A discloses "a low-temperature asphalt-coated foamed carbon SIBs carbon-based negative electrode material and its preparation method". This method mixes foamed carbon with asphalt and then carbonizes it in a tubular furnace to obtain an asphalt-coated foamed carbon negative electrode material. This asphalt-coated foamed carbon negative electrode material has high specific capacity and high coulombic efficiency, but the heat treatment temperature is high and the energy consumption is large, which makes it impossible to produce it on a large scale industrially and has low practicality. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide an asphalt-based hard carbon negative electrode material and a preparation method and application thereof. The asphalt-based hard carbon negative electrode material prepared by the present invention can improve the reversible capacity and service life of industrial new energy batteries, and at the same time reduce production costs.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a pitch-based hard carbon negative electrode material, comprising the following steps:
[0008] The asphalt raw material, the organic solvent and the oxidant are mixed, and an oxidation reaction is carried out under protective gas conditions. The solid obtained by the first solid-liquid separation of the obtained suspension is first dried to obtain an asphalt-based hard carbon precursor;
[0009] The asphalt-based hard carbon precursor, the negative electrode material and the solvent thermal reaction solvent are mixed to carry out a solvent thermal reaction. The solid obtained by the second solid-liquid separation of the obtained reaction liquid is boiled with an acid solution, washed to neutrality, and dried for a second time to obtain the asphalt-based hard carbon negative electrode material.
[0010] Preferably, the asphalt raw material includes petroleum-based asphalt and / or coal-based asphalt.
[0011] Preferably, the organic solvent includes one or more of xylene, trichloroethylene, carbon disulfide and carbon tetrachloride.
[0012] Preferably, the mass ratio of the asphalt raw material to the organic solvent is 1:1-10.
[0013] Preferably, the solvent thermal reaction solvent is a mixture of N,N-dimethylformamide and anhydrous ethanol, and the mass ratio of N,N-dimethylformamide to anhydrous ethanol is 2 to 5:1.
[0014] Preferably, the temperature of the oxidation reaction is 80-150° C., and the insulation time is 1-3 hours.
[0015] Preferably, based on the mass of the asphalt raw material, the flow rate of the protective gas is 0.1 to 2 L / min / kg.
[0016] The present invention also provides a pitch-based hard carbon negative electrode material prepared by the preparation method described in the above technical solution, comprising a negative electrode material and a pitch-based hard carbon coated on the surface of the negative electrode material.
[0017] Preferably, the softening point of the asphalt-based hard carbon negative electrode material is ≥200° C., the charge specific capacity is 385 to 395 mA·h / g, the discharge specific capacity is 345 to 370 mA·h / g, and the coulombic efficiency is 90 to 95%.
[0018] The present invention also provides the application of the asphalt-based hard carbon negative electrode material described in the above technical solution in new energy batteries.
[0019] The present invention provides a method for preparing an asphalt-based hard carbon negative electrode material, comprising the following steps: mixing an asphalt raw material, an organic solvent and an oxidant, performing an oxidation reaction under protective gas conditions, performing a first solid-liquid separation on the obtained suspension to obtain a solid, thereby obtaining an asphalt-based hard carbon precursor; mixing the asphalt-based hard carbon precursor, the negative electrode material and a solvent thermal reaction solvent to perform a solvent thermal reaction, performing a second solid-liquid separation on the obtained reaction liquid to obtain a solid, boiling the solid with an acid solution, washing it to neutrality, and performing a second drying to obtain an asphalt-based hard carbon negative electrode material.
[0020] In the present invention, the asphalt raw material is dissolved in an organic solvent, and a highly dispersed microparticle suspension is generated under the action of an oxidant. The oxidant plays a role in oxidizing some unsaturated hydrocarbon bonds, and also provides free hydroxyl groups on the surface of the asphalt suspension particles. The protective gas introduced can take away the dissolved oxygen produced by the incomplete reaction, and the positive pressure environment in the reactor is conducive to the attachment of hydroxyl free groups. The negative electrode material and the asphalt-based hard carbon precursor form a stable carbon particle coating structure through carbonization during the hydrothermal process. The solvent thermal reaction solvent avoids the carbon particles from reacting with water molecules in a water-containing environment, thereby reducing the carbon coating amount. Boiling and rinsing with an acid solution can take away impurities (such as oily substances and pyrolysis products, etc.) on the surface of the coated negative electrode material, thereby improving the surface cleanliness and electrochemical properties of the coated material. The method has a short process flow, low production cost, and short production time. The prepared asphalt-based hard carbon negative electrode material has the characteristics of high surface coating, uniform coating, and small coating layer particles, and is easy to realize industrial application. The asphalt-based hard carbon negative electrode material prepared by this method is used in the negative electrode of new energy batteries to improve the reversible capacity and cyclability, which can solve the problem of short service life of new energy batteries and improve their safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope image of the pitch-based hard carbon negative electrode material prepared in Example 1 of the present invention;
[0022] Figure 2 This is a scanning electron microscope image of the asphalt-based hard carbon negative electrode material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0023] The present invention provides a method for preparing a pitch-based hard carbon negative electrode material, comprising the following steps:
[0024] The asphalt raw material, the organic solvent and the oxidant are mixed, and an oxidation reaction is carried out under protective gas conditions. The solid obtained by the first solid-liquid separation of the obtained suspension is first dried to obtain an asphalt-based hard carbon precursor;
[0025] The asphalt-based hard carbon precursor, the negative electrode material and the solvent thermal reaction solvent are mixed to carry out a solvent thermal reaction. The solid obtained by the second solid-liquid separation of the obtained reaction liquid is boiled with an acid solution, washed to neutrality, and dried for a second time to obtain the asphalt-based hard carbon negative electrode material.
[0026] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used in the preparation, and commercially available products known to those skilled in the art can be used.
[0027] The present invention mixes asphalt raw materials, organic solvents and oxidants, performs oxidation reaction under protective gas conditions, performs first solid-liquid separation of the obtained suspension and obtains a solid that is first dried to obtain an asphalt-based hard carbon precursor.
[0028] In the present invention, the asphalt raw material preferably includes petroleum-based asphalt and / or coal-based asphalt, and is more preferably petroleum-based asphalt; the organic solvent preferably includes one or more of xylene, trichloroethylene, carbon disulfide and carbon tetrachloride, and is more preferably xylene, trichloroethylene or carbon disulfide; the oxidant preferably includes hydrogen peroxide or ozone, and is more preferably hydrogen peroxide; when the oxidant is ozone, the ozone is preferably used in the form of an ozone aqueous solution; the concentration of the ozone aqueous solution is preferably 10 to 20 mg / L, and is more preferably 12 to 15 mg / L.
[0029] In the present invention, the mass ratio of the asphalt raw material and the organic solvent is preferably 1:1-10, more preferably 1:2-5; the mass ratio of the total mass of the asphalt raw material and the organic solvent to the mass of hydrogen peroxide is preferably 10:1-5, more preferably 10:2-3; the concentration of the hydrogen peroxide is preferably 1-30%, more preferably 5-10%; the mass ratio of the total mass of the asphalt raw material and the organic solvent to the mass of the ozone aqueous solution is preferably 10:1-5, more preferably 10:2-3.
[0030] In the present invention, the asphalt raw material, organic solvent and oxidant are preferably mixed as follows: the asphalt raw material and the organic solvent are first mixed and stirred, and the resulting mixed solution is then mixed with the oxidant; the stirring is preferably carried out at room temperature; the stirring rate is preferably 200 to 500 r / min, more preferably 300 to 400 r / min; the stirring time is preferably 0.5 to 2 h, more preferably 1 to 1.5 h.
[0031] In the present invention, the temperature of the oxidation reaction is preferably 80-150°C, more preferably 100-120°C, and the insulation time is preferably 1-3h, more preferably 1.5-2.5h; the oxidation reaction is preferably carried out under stirring; the stirring rate is preferably 120-360r / min, more preferably 240-300r / min; the oxidation reaction is preferably carried out in a reactor; the pressure in the reactor is preferably 0.1-1.2MPa, more preferably 0.2-0.8MPa.
[0032] In the present invention, the shielding gas preferably includes nitrogen or an inert gas, more preferably nitrogen; the inert gas preferably includes argon or helium, more preferably argon; based on the mass of the asphalt raw material, the flow rate of the shielding gas is preferably 0.1 to 2 L / min / kg, more preferably 0.5 to 1 L / min / kg.
[0033] In the present invention, the asphalt raw material is dissolved in an organic solvent and a highly dispersed particulate suspension is generated under the action of an oxidant such as hydrogen peroxide. The hydrogen peroxide plays a role in oxidizing some unsaturated hydrocarbon bonds. At the same time, the hydrogen peroxide also provides free hydroxyl groups on the surface of the asphalt suspension particles. The protective gas introduced can take away the dissolved oxygen produced by incomplete reaction. The positive pressure environment in the reactor is conducive to the attachment of hydroxyl free radicals.
[0034] In the present invention, the first solid-liquid separation is preferably filtration; the temperature of the first drying is preferably 80-150° C., more preferably 100-120° C.; the time of the first drying is preferably 1-3 h, more preferably 1.5-2 h.
[0035] After obtaining the pitch-based hard carbon precursor, the present invention mixes the pitch-based hard carbon precursor, the negative electrode material and a solvent thermal reaction solvent to perform a solvent thermal reaction.
[0036] In the present invention, the solvent thermal reaction solvent is preferably a mixture of N,N-dimethylformamide (DMF) and anhydrous ethanol, and the mass ratio of N,N-dimethylformamide and anhydrous ethanol is preferably 2-5:1, more preferably 3-4:1; the mass ratio of the asphalt-based hard carbon precursor, the negative electrode material and the solvent thermal reaction solvent is preferably 1:10-30:50-100, more preferably 1:10-20:50-80. The present invention has no special requirements for the negative electrode material, and the negative electrode material well known in the art can be used. In an embodiment of the present invention, the negative electrode material is a graphite sheet, a nanocarbon sphere or a carbon nanotube.
[0037] In the present invention, the temperature of the solvothermal reaction is preferably 100-150°C, more preferably 110-120°C, and the insulation time is preferably 3-8h, more preferably 5-7h; the solvothermal reaction is preferably carried out under stirring; the stirring rate is preferably 60-120r / min, more preferably 90-110r / min; the solvothermal reaction is preferably carried out in a reactor; the pressure in the reactor is preferably 0.3-1.5MPa, more preferably 0.5-0.9MPa.
[0038] In the present invention, the negative electrode material and the asphalt-based hard carbon precursor form a stable carbon particle coating structure through carbonization during the hydrothermal process, and the solvent thermal reaction solvent (DMF and anhydrous ethanol) prevents the carbon particles from reacting with water molecules in a water-containing environment, thereby reducing the carbon coating amount.
[0039] After the solvent thermal reaction, the present invention performs a second solid-liquid separation on the reaction solution obtained by the solvent thermal reaction to obtain a solid, boils it with an acid solution, washes it to neutrality, and performs a second drying to obtain a pitch-based hard carbon negative electrode material.
[0040] In the present invention, the second solid-liquid separation is preferably filtration; the acid solution is preferably oxalic acid solution, nitric acid solution or acetic acid solution, more preferably oxalic acid solution or acetic acid solution; the mass fraction of the acid solution is preferably 0.5-3%, more preferably 1-2%; the mass ratio of the solid obtained by the second solid-liquid separation to the acid solution is preferably 1:50-100, more preferably 1:60-80; the boiling treatment time is preferably 30-90 min, more preferably 50-70 min; the washing is preferably rinsing; the reagent used for washing is preferably deionized water; the second drying temperature is preferably 80-150°C, more preferably 100-120°C; the second drying time is preferably 3-8h, more preferably 5-7h.
[0041] The boiling and washing of the acid solution in the present invention can remove impurities (such as oily substances and pyrolysis products, etc.) on the surface of the coated negative electrode material, thereby improving the surface cleanliness and electrochemical properties of the coated material.
[0042] The present invention first disperses the asphalt raw material, then forms free hydroxyl groups on the asphalt surface through the action of hydrogen peroxide, then coats the surface of the negative electrode material with an asphalt-based hard carbon coating layer through a solvent thermal reaction, and finally removes the residual impurities on the surface through acid washing to obtain an asphalt-based hard carbon negative electrode material. The preparation method has a short process flow, low operating cost, and short production time. The prepared asphalt-based hard carbon negative electrode material has the characteristics of high surface coating, uniform coating, and small coating layer particles. Its application in the negative electrode of new energy batteries plays a role in improving reversible capacity and cyclability, and can solve the problem of short service life of new energy batteries and improve their safety.
[0043] The present invention also provides a pitch-based hard carbon negative electrode material prepared by the preparation method described in the above technical solution, comprising a negative electrode material and a pitch-based hard carbon coated on the surface of the negative electrode material.
[0044] In the present invention, the particle size of the pitch-based hard carbon negative electrode material is preferably 0.1 to 100 μm, more preferably 1 to 20 μm, and the specific surface area is preferably ≥50 m 2 / g, more preferably ≥100m 2 / g, the softening point is preferably ≥200°C, more preferably 204°C, the charge specific capacity is preferably 385-395mA·h / g, more preferably 387.3mA·h / g, 390.1mA·h / g or 392.5mA·h / g, the discharge specific capacity is preferably 345-370mA·h / g, more preferably 349.1mA·h / g, 368.4mA·h / g or 367.5mA·h / g, and the coulombic efficiency is preferably 90-95%, more preferably 90.13%, 93.87% or 94.21%.
[0045] The asphalt-based hard carbon negative electrode material prepared by the present invention has the characteristics of high surface coverage, uniform coating, and small coating layer particles, and is easy to realize industrial application. Its application in the negative electrode of new energy batteries plays a role in improving the reversible capacity and cyclability, can solve the problem of short service life of new energy batteries, and improve their safety.
[0046] The present invention also provides the application of the asphalt-based hard carbon negative electrode material described in the above technical solution in new energy batteries.
[0047] The present invention has no special limitation on the application of the asphalt-based hard carbon negative electrode material in new energy batteries, and any application method known in the art may be used.
[0048] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0049] Example 1
[0050] Petroleum-based asphalt and xylene were mixed in a mass ratio of 1:5 and stirred at a rate of 300 r / min for 0.5 h at room temperature. The resulting mixed solution and hydrogen peroxide (concentration of 10%) were added to a reactor in a mass ratio of 10:3, and the oxidation reaction was carried out at 120°C and 120 r / min for 3 h. While stirring, nitrogen was introduced at a flow rate of 2 L / min / kg (based on the mass of petroleum-based asphalt) and the pressure in the reactor was maintained at 0.1 MPa. The solid obtained by filtering the suspension obtained after the oxidation reaction was dried at 150°C for 1 h to obtain a pitch-based hard carbon precursor;
[0051] The asphalt-based hard carbon precursor, graphite sheet, and solvothermal reaction solvent (DMF and anhydrous ethanol in a mass ratio of 2:1) are added to the reactor in a mass ratio of 1:30:100, and the solvent thermal reaction is carried out at 100°C with stirring at a speed of 60r / min for 8 hours. During the solvothermal reaction, the pressure in the reactor is maintained at 1.5MPa. The reaction liquid obtained after the solvothermal reaction is filtered and the obtained solid is boiled with a dilute oxalic acid solution with a mass fraction of 0.5% for 50 minutes. The mass ratio of the solid to the dilute oxalic acid solution is 1:50. The solid is rinsed with deionized water until neutral, and then dried at 120°C for 3 hours to obtain an asphalt-based hard carbon negative electrode material.
[0052] The properties of the pitch-based hard carbon negative electrode material obtained in this embodiment are shown in Table 1. The pitch-based hard carbon negative electrode material prepared by the present invention has a charge capacity of 387.3 mA·h / g, a discharge capacity of 349.1 mA·h / g, and a coulombic efficiency of 90.13%. Figure 1 It can be seen that the asphalt-based hard carbon with a particle size of 0.5 μm is evenly attached to the surface of the asphalt-based hard carbon negative electrode material observed by electron microscopy.
[0053] Table 1 Properties of asphalt-based hard carbon negative electrode materials
[0054]
[0055] Example 2
[0056] Petroleum-based asphalt and trichloroethylene were mixed in a mass ratio of 1:10 and stirred at a rate of 200 r / min for 1 h at room temperature. The resulting mixed solution and hydrogen peroxide (concentration of 1%) were added to a reactor in a mass ratio of 10:1, and the oxidation reaction was carried out at 80°C and 360 r / min with stirring for 2 h. While stirring, nitrogen was introduced at a flow rate of 0.5 L / min / kg (based on the mass of petroleum-based asphalt) and the pressure in the reactor was maintained at 0.8 MPa. The solid obtained by filtering the suspension obtained after the oxidation reaction was dried at 120°C for 2 h to obtain a pitch-based hard carbon precursor;
[0057] The asphalt-based hard carbon precursor, nano-carbon spheres, and solvothermal reaction solvent (DMF and anhydrous ethanol in a mass ratio of 3:1) are added to the reactor in a mass ratio of 1:10:80, and the solvothermal reaction is carried out at 150°C with stirring at a speed of 90r / min for 3 hours. During the solvothermal reaction, the pressure in the reactor is maintained at 0.3MPa. The solid obtained by filtering the reaction liquid after the solvothermal reaction is boiled for 30 minutes with a dilute acetic acid solution with a mass fraction of 2%, and the mass ratio of the solid to the dilute acetic acid solution is 1:80. It is rinsed with deionized water until neutral, and then dried at 150°C for 8 hours to obtain a asphalt-based hard carbon negative electrode material.
[0058] The pitch-based hard carbon negative electrode material prepared by the present invention has a charge specific capacity of 392.5 mA·h / g, a discharge specific capacity of 368.4 mA·h / g, and a coulombic efficiency of 93.87%. Figure 2 It can be seen that the asphalt-based hard carbon with a particle size of 0.5 μm is evenly attached to the surface of the asphalt-based hard carbon negative electrode material observed by electron microscopy.
[0059] Example 3
[0060] Coal-based asphalt and carbon disulfide were mixed in a mass ratio of 1:1 and stirred at a rate of 500r / min for 2h at room temperature. The resulting mixed solution and hydrogen peroxide (concentration of 30%) were added to a reactor in a mass ratio of 10:5, and the oxidation reaction was carried out at 150°C and 240r / min with stirring for 1h. While stirring, nitrogen was introduced at a flow rate of 0.1L / min / kg (based on the mass of coal-based asphalt) and the pressure in the reactor was maintained at 1.2MPa. The solid obtained by filtering the suspension obtained after the oxidation reaction was dried at 80°C for 3h to obtain a asphalt-based hard carbon precursor;
[0061] The asphalt-based hard carbon precursor, nanotubes, and solvothermal reaction solvent (DMF and anhydrous ethanol in a mass ratio of 5:1) are added to the reactor in a mass ratio of 1:20:50, and the solvothermal reaction is carried out at 120°C with stirring at a speed of 120r / min for 6 hours. During the solvothermal reaction, the pressure in the reactor is maintained at 0.9MPa. The solid obtained by filtering the reaction liquid after the solvothermal reaction is boiled with a dilute nitric acid solution with a mass fraction of 3% for 90 minutes. The mass ratio of the solid to the dilute nitric acid solution is 1:100, and it is rinsed with deionized water until neutral, and then dried at 80°C for 6 hours to obtain a asphalt-based hard carbon negative electrode material.
[0062] The asphalt-based hard carbon negative electrode material prepared by the present invention has a charge specific capacity of 390.1 mA·h / g, a discharge specific capacity of 367.5 mA·h / g, and a coulombic efficiency of 94.21%.
[0063] Comparative Example 1 (without adding organic solvent)
[0064] Petroleum-based asphalt and deionized water were mixed in a mass ratio of 1:10 and stirred at 300 r / min for 2 h at room temperature. The resulting mixture and hydrogen peroxide (concentration of 20%) were added to a reactor in a mass ratio of 10:5, and the oxidation reaction was carried out at 120°C and 240 r / min for 3 h. While stirring, nitrogen was introduced at a flow rate of 0.8 L / min / kg (based on the mass of petroleum-based asphalt) and the pressure in the reactor was maintained at 1.0 MPa. The suspension obtained after the oxidation reaction was filtered and the solid obtained was dried at 110°C for 2 h to obtain an asphalt-based hard carbon precursor;
[0065] The asphalt-based hard carbon precursor, graphite sheet, and solvothermal reaction solvent (DMF and anhydrous ethanol in a mass ratio of 2:1) are added to the reactor in a mass ratio of 1:10:75, and the solvothermal reaction is carried out at 130°C with stirring at a speed of 100 r / min for 6 hours. The pressure in the reactor is maintained at 0.7 MPa during the solvothermal reaction. The solid obtained by filtering the reaction liquid after the solvothermal reaction is boiled with a dilute oxalic acid solution with a mass fraction of 2% for 50 minutes. The mass ratio of the solid to the dilute oxalic acid solution is 1:60. It is rinsed with deionized water until neutral, and then dried at 110°C for 6 hours to obtain an asphalt-based hard carbon negative electrode material.
[0066] The asphalt-based hard carbon negative electrode material prepared by the present invention has a charge specific capacity of 331.4 mA·h / g, a discharge specific capacity of 241.3 mA·h / g, and a coulombic efficiency of 72.81%.
[0067] Comparative Example 2 (without adding hydrogen peroxide)
[0068] Petroleum-based asphalt and carbon tetrachloride were mixed in a mass ratio of 1:7 and stirred at a rate of 500 r / min for 1 h at room temperature. The resulting mixed solution and deionized water were added to a reactor in a mass ratio of 10:5, and the oxidation reaction was carried out at 90°C and 200 r / min with stirring for 3 h. While stirring, nitrogen was introduced at a flow rate of 2 L / min / kg (based on the mass of petroleum-based asphalt) and the pressure in the reactor was maintained at 0.5 MPa. After the oxidation reaction, the solid obtained by filtering the suspension was dried at 90°C for 3 h to obtain a pitch-based hard carbon precursor;
[0069] The asphalt-based hard carbon precursor, graphite sheet, and solvothermal reaction solvent (DMF and anhydrous ethanol in a mass ratio of 3:1) are added to the reactor in a mass ratio of 1:15:60, and the solvothermal reaction is carried out at 110°C with stirring at a speed of 100 r / min for 5 hours. The pressure in the reactor is maintained at 0.5 MPa during the solvothermal reaction. The solid obtained by filtering the reaction liquid after the solvothermal reaction is boiled with a dilute acetic acid solution with a mass fraction of 0.8% for 45 minutes. The mass ratio of the solid to the dilute acetic acid solution is 1:50, and it is rinsed with deionized water until neutral, and then dried at 140°C for 4 hours to obtain an asphalt-based hard carbon negative electrode material.
[0070] The asphalt-based hard carbon negative electrode material prepared by the present invention has a charge specific capacity of 325.6 mA·h / g, a discharge specific capacity of 257.5 mA·h / g, and a coulombic efficiency of 79.08%.
[0071] Comparative Example 3 (solvent thermal reaction solvent is replaced by deionized water)
[0072] Petroleum-based asphalt and xylene were mixed in a mass ratio of 1:5 and stirred at a rate of 300 r / min for 1.5 h at room temperature. The resulting mixed solution and hydrogen peroxide (concentration of 12%) were added to a reactor in a mass ratio of 10:3, and the oxidation reaction was carried out at 85°C and 180 r / min with stirring for 2 h. While stirring, nitrogen was introduced at a flow rate of 1.5 L / min / kg (based on the mass of petroleum-based asphalt) and the pressure in the reactor was maintained at 1.0 MPa. The solid obtained by filtering the suspension obtained after the oxidation reaction was dried at 130°C for 1 h to obtain a pitch-based hard carbon precursor;
[0073] The asphalt-based hard carbon precursor, graphite sheet and deionized water are added to the reactor in a mass ratio of 1:25:55, and the solvent thermal reaction is carried out at 120°C with stirring at 80r / min for 7 hours. The pressure in the reactor is maintained at 0.6MPa during the solvent thermal reaction. The solid obtained by filtering the reaction liquid after the solvent thermal reaction is boiled with a dilute oxalic acid solution with a mass fraction of 1.5% for 50 minutes. The mass ratio of the solid to the dilute oxalic acid solution is 1:70. It is rinsed with deionized water until neutral, and then dried at 120°C for 7 hours to obtain an asphalt-based hard carbon negative electrode material.
[0074] The asphalt-based hard carbon negative electrode material prepared by the present invention has a charge specific capacity of 314.7 mA·h / g, a discharge specific capacity of 256.8 mA·h / g, and a coulombic efficiency of 81.60%.
[0075] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a pitch-based hard carbon negative electrode material, characterized in that: The following steps are involved: The asphalt raw material, the organic solvent and the oxidant are mixed, and an oxidation reaction is carried out under protective gas conditions. The solid obtained by the first solid-liquid separation of the obtained suspension is first dried to obtain an asphalt-based hard carbon precursor; The asphalt-based hard carbon precursor, the negative electrode material and the solvent thermal reaction solvent are mixed to carry out a solvent thermal reaction. The solid obtained by the second solid-liquid separation of the obtained reaction liquid is boiled with an acid solution, washed to neutrality, and dried for a second time to obtain the asphalt-based hard carbon negative electrode material.
2. The preparation method according to claim 1, characterized in that: The asphalt raw material includes petroleum-based asphalt and / or coal-based asphalt.
3. The preparation method according to claim 1, characterized in that: The organic solvent includes one or more of xylene, trichloroethylene, carbon disulfide and carbon tetrachloride.
4. The preparation method according to claim 1, 2 or 3, characterized in that: The mass ratio of the asphalt raw material to the organic solvent is 1:1-10.
5. The preparation method according to claim 1, characterized in that: The solvent thermal reaction solvent is a mixture of N,N-dimethylformamide and anhydrous ethanol, and the mass ratio of the N,N-dimethylformamide to the anhydrous ethanol is 2 to 5:
1.
6. The preparation method according to claim 1, characterized in that: The temperature of the oxidation reaction is 80-150° C., and the insulation time is 1-3 hours.
7. The preparation method according to claim 1, characterized in that: Based on the mass of the asphalt raw material, the flow rate of the protective gas is 0.1-2 L / min / kg.
8. The pitch-based hard carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The invention comprises a negative electrode material and asphalt-based hard carbon coated on the surface of the negative electrode material.
9. The pitch-based hard carbon negative electrode material according to claim 8, characterized in that: The softening point of the asphalt-based hard carbon negative electrode material is ≥200° C., the charge specific capacity is 385-395 mA·h / g, the discharge specific capacity is 345-370 mA·h / g, and the coulomb efficiency is 90-95%.
10. Application of the asphalt-based hard carbon negative electrode material according to claim 8 or 9 in new energy batteries.
Citation Information
Patent Citations
Low-temperature asphalt coated foamy carbon SIBs carbon-based negative electrode material and preparation method thereof
CN118145620A